Intergroup Relations in Integrated Schools: A Glimpse Inside Interdistrict Magnet Schools - Bifulco, Robert; Buerger, Christian; Cobb, Casey (Education Policy Analysis Archives, 2012)
The frequency and quality of intergroup contact within racially and ethnically diverse schools has potentially important implications for the achievement of desegregation goals. The analyses presented here use survey data to assess intergroup contact within a sample of ten interdistrict magnet schools in Connecticut. Findings indicate frequent intergroup interactions within interdistrict magnet schools, but also that the perceived quality of intergroup relations differs across racial groups and both the frequency and quality of intergroup contact varies considerably across schools. Students who report higher quality intergroup relations in their school also tend to report more positive academic environments and more positive attitudes towards other groups. Together these findings indicate that attention must be paid to intergroup relations within diverse schools if the goals of integrated schooling are to be realized.